EFFECT HYDRAULIC AGITATION USING ANAEROBIC BIOFILTER FOR TREATED DOMESTIC WASTEWATER - Nur Indradewi Oktavitri; Agoes Soegianto; Trisnadi Widyaleksono C. Putranto; Angsukma P. Dewayanti; Adam L.H. Suryawan (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2012)
The objective of this study was to investigate the effi ciency the TSS reduction of domestic wastewater by using hydraulic agitation in anaerobic biofi lter. The reactor consists of four columns. Each column has a sampling point. Upfl ow direction was operated in reactor in order to maximize the hydraulic agitation. Gravel was used as fi lter media to support the growth of biofi lm. The reactor treated wastewater of FST Airlangga University canteen which contains 8237.463 mg/l of TSS. Flow used during processing was 0.3 ml/min. Sampling TSS were performed on days 7, 14, 21, and 28. The results showed that the effi ciency of TSS were 64.57%, 76.16%, 94.23% and 98.46% respectively. The average TSS removal was 83.36%.